EMOTIONAL EDUCATION OF PRESCHOOL CHILDREN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article, it was explained what methods should be used by parents in emotional education, emotional education and moral education of preschool children in the family.